The Customer’s Perception Towards Islamic and Conventional Banks in Algeria - Abdelhak Taalbi; Dr. Nur Farhah Binti Mahadi; Dr.Ashurov Sharofiddin (Faculty of Islamic Business and Management, 2023)
This study aims to know the perception of customers towards Islamic and conventional banks in Algeria, and to help banks operating in Algeria focus on the most important factors for customers, improve their ways of dealing with customers, and focus on these standards in its promotional program to reach the target segment. In order to achieve this, the researcher has chosen a random sample of (203) size from customers of Islamic and conventional banks in Algeria, the questionnaire was approved to collect data, and it was subject to honesty and reliability standards. The researcher used one approach to analyze the results of the research; the first is the descriptive analytical approach to answer the research question. The study reached several results, the most important of which are the following: 1. The majority of customers are fully aware of the principle of Islamic and conventional banking in Algeria. They were able to answer all the questions related to customer perception, which indicates their good understanding of the Islamic and conventional banking principle. In other words, the higher the awareness, the more effective the customer awareness of Islamic and conventional banks.